Successful Treatment of Upadacitinib in Prurigo Nodularis: A Case Report and Review of the Literature - Li B; Yao W; Diao R; Yang B; Wang Y; Li T; Ge L; Wang H (International Medical Case Reports Journal)
Bohui Li,1 Wo Yao,1 Ran Diao,1 Boyun Yang,1 Yongfang Wang,1 Ting Li,1 Liuya Ge,2 Huiying Wang1 1Department of Allergy and Clinical Immunology, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, 310009, People’s Republic of China; 2Outpatient Care Department, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, 310009, People’s Republic of ChinaCorrespondence: Huiying Wang, Department of Allergy and Clinical Immunology, The Second Affiliated Hospital of Zhejiang University School of Medicine, 88 Jiefang Road, Shangcheng District, Hangzhou, Zhejiang Province, 310009, People’s Republic of China, Email marywang@zju.edu.cnBackground: Prurigo nodularis (PN), while rare, presents significant clinical challenges due to its diverse pathogenesis and presentation. Effective therapy recommendations for PN remain limited. Upadacitinib, an oral highly selective type 1 Janus-associated kinase (JAK, Intracellular tyrosine kinases that phosphorylate cytokine receptors). Inhibitor plays an excellent role in alleviating itching in atopic dermatitis (AD). This is a report on the treatment of PN with upadacitinib, which offers a new option for refractory PN.Case Presentation: We share our successful treatment experience of upadacitinib on a 43-year-old female patient with refractory PN failing to conventional therapies. She showed significant improvement at the follow-up visits and no obvious adverse effects happened. We also reviewed published case reports of PN patients and PN-related review researches and made a comprehensive discussion of the potential mechanism of JAK1 inhibitors in treating PN.Conclusion: Upadacitinib may be a safe and potent alternative for patients with refractory PN.Keywords: prurigo nodularis, upadacitinib, janus kinase inhibitor, immunotherapy, dermatology